Teacher Perception on the Implementation of (Information and Communcation Technology) ICT-Based Training in Managing Practicum of Physics - Y Surtiana; W Setiawan; I Kaniawati (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to reveal physics teachers’ perception on the implementation ofInformation and Communication Technology (ICT)-based training to improve theirprofessionalism in practicum management. There are 40 physics teachers from 25 differentsenior high schools in Bandung, Indonesia, involved in this study. This study is based onqualitative methodology using a descriptive approach. Data were collected using closedquestionnaires with interviews added Perceptions consist of 3 (three) types of spirit(enthusiasm), visibility (literacy), and absorption (success). Training is a professionalismimprovement program using andriod-based smartphones. The results show that the enthusiasmlevel reaches 85% of the participants, the visibility reaches 50% of the participants, and 70% ofthe participants identifies appropriate training. Based on the results obtained can be stated thatthe program improves the professionalism of teachers in managing practicum can be doneusing andriod-based smartphone. ICT-based practice management training program is moreeffective and efficient, and focuses on 21st century development towards Indonesia Emas(Golden Indonesia) 2045.